Assessment of Reading Comprehension in Mexican University Students´ of Applied Mathematics and Computing: Evaluación de la comprensión lectora en alumnos universitarios mexicanos de matemáticas aplicadas y computación (Papeles, 2022)
Introduction: This study evaluated reading comprehension levels and related them to the use of reading strategies, reading motivation, and sociodemographic and academic variables, in Physics-Mathematics and Engineering students. Methodology: Applied instruments: Self-Reporting of Sociodemographic and Academic Data (ADSA), the Inventory of Metacognive Strategies and Motivation for Reading (IEMML) and the Instrument for Measuring Reading Understanding in University Students (ICLAU). A total of 309 students collaborated, 218 were men and 91 women, 69 % were first-year and 31 % seniors’ students. Results and discussion: Results indicated that students showed a low level of reading comprehension (53 %) and reported using 69 % of the strategies evaluated by the instrument. A significant relationship between the total scores of both instruments was found. Similarly, significant differences in the IEMML score based on the time spent reading were found. Conclusions: Results are discussed in terms of the influence students’ training area plans and programs can have on reading comprehension and the use of strategies.on and the use of strategies.
Keywords: Reading comprehension; reading strategies; university students; motivation; university career